Liver-stage vaccines for malaria - Longley, RJ (2013)
The development of an efficacious P. falciparum malaria vaccine remains a top priority. Pre-erythrocytic vaccine efforts have traditionally focussed on two well- known antigens, CSP and TRAP, yet thousands of antigens are expressed throughout the liver-stage. The work described in this thesis aimed to assess the ability of other pre-erythrocytic antigens to induce an immune response and provide protective efficacy against transgenic parasites in a mouse model. Research undertaken in our laboratory has demonstrated the ability of prime-boost viral vectored sub-unit vaccination regimens to elicit high levels of antigen-specific T cells. Eight candidate antigens were therefore expressed individually in the viral vectors ChAd63 and MVA. Two antigens, PfLSA1 and PfLSAP2, were identified that confer greater protective efficacy in inbred mice than either CSP or TRAP. PfLSA1 was also able to induce almost complete sterile efficacy in outbred mice, suggesting this vaccine should be assessed in a clinical trial. Immune responses to the candidate antigens were also assessed in human volunteers following their first exposure to controlled malaria infection. The antigen TRAP was further characterised by epitope mapping in volunteers vaccinated with ChAd63-MVA ME-TRAP. However, no functional T cell assay exists to measure inhibition of P. falciparum liver-stage parasites. An improved murine in vitro T cell killing assay was developed, and preliminary experiments were conducted that demonstrate the potential and promise of a P. falciparum T cell killing assay. Such assays will not only allow mechanistic studies to be undertaken, but could also change the way we screen pre-clinical liver-stage vaccines.